The tribal council and its role in the continuation of the B'laan culture of Tanpakan, South Cotabato - Corpuz, Lady Lynice S.
The culture of B'laan in Tampakan, South Cotabato is considered at its peak of dramatic change. The B'laans have been assimilated and accultured by Christian migrants, the Bisaya/Kristiano, the term used by the B'Laans to refer to inhabitants from Luzon, Visayas, and various parts of Midnanao who settled in South Cotabato in the years 1930's and 1940's. Some of the B'laans customs, beliefs and traditions are no longer observed today. Their concept of sunggod (dowry), polygamous marriage, and m'ngayoh (manhunting) are some of those cast off. From the point of view of the B'laan tribal leaders, the present generation of the B'laan are not as rigid as their ancestors in terms of following and preserving the B'laan culture. The tribal chieftains perceived themselves as important individuals in the preservation of their culture. They always take the lead and courage the B'laans to resist changes that could lead in their assimilation. It keeps on coming back to them that they are used to be majority in Tampakan and not the settlers. What has been left to them today is their diminishing culture. What they keep to consider at present is the continuation of their remaining traditions particularly its suitability in the modern world.